"Chemo Brain"—Is Cancer Survivorship Related to Later-Life Cognition? Findings From the Health and Retirement Study. (September 2013) - Porter, Kristen E.
Objective: Studies have shown a correlation between cancer and cognition referred to as "chemo brain." This study investigated the relationship between cancer and later-life cognition using nationally representative data.Method: Analysis of the 2006 Health and Retirement Study investigated the (a) effects of cancer survivorship on the total cognition score using linear regression in adults age 65+ ( n = 9, 814) and (b) the effects of cancer treatment on the total recall index using linear regression in adults age 50+ ( n = 657).Results: Total cognition score is not associated with cancer survivorship. The association between long-term cancer survivorship and cognition score was significant ( p < .05; b = .276). Total recall index is not associated with chemotherapy.Discussion: These results support other research suggesting that chemo brain may be biased by expectation as well as favored by research that relies upon self-reported cognitive measures versus cognitive testing. The study was limited by the cross-sectional design.